Primordialisme Ritual Umat Hindu Dalam Menjaga Eksistensi Pura di Lombok - Arini , Ni Made; Yudhiarsana , I Made Agus; Sukendri, Nengah; Istri Anom, Anak Agung; Wiguna, Ida Bagus Alit Arta (Jurnal Penelitian Agama Hindu, 2023)
This study aims to be able to reveal various phenomena that arise regarding the implementation of primordialism, the factors that influence the resilience of Hindu ritual primordialism and analyze the implications of ritual primordialism for Balinese ethnic Hindus in Lombok, according to the traditions, customs and culture of Balinese Hindus in implementing religious rituals or ceremonies. Social dynamics and technological developments have an influence, both directly and indirectly, on attitudes, values, and patterns of behavior, as well as the perspective of each individual in a community as part of the larger society. Likewise with the Balinese Hindu community in Lombok. The influence of ideology that comes from sampradaya which offers all new and different things and is considered to have more value, than what has been believed so far, can lead to changes in the thinking or ideology of each individual. So it is necessary to study the ritual primordialism of Balinese Hindus in Lombok. This study uses a qualitative descriptive research type with data sources in the form of non-participant observations, structured interviews and documents. The location of the temple was determined purposefully. The data is then classified, reduced, and interpreted, then the results of the analysis are presented in a narrative manner. The results obtained in this study are firstly the implementation of ritual primordialism for Balinese Hindus still applying customs, culture and traditions, regarding the series of ceremonies and ceremonies used, by applying the yadnya level as a form of ritual adaptation. Second, Hindu ritual primordialism has strengths in the form of social interaction and acculturation of Balinese and Sasak ethnic cultures, as well as community economic turnover. The three ethnic Balinese Hindus still have high primordial resistance, which has implications for the maintenance of ritual traditions and the existence of temples in Lombok based on religious emotions, belief systems, rite systems and religious ritual equipment, and religious groups and their systems that are still maintained.